Islam dan Doktrin Ekonomi - Muhammad Zaki (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Islam is a revelation sent down by Allah SWT. to His apostles to regulate all aspects of life both vertically and horizontally which contain broad guidance for life, while at the same time giving essential values to that life. Islam also means obedience, obedience to the will and law of Allah SWT. and fear Him who was sent down to organize human life in this world and the hereafter. Islamic teachings originate from the Quran, sunnah and ijtihad. The main points of Islamic teachings are believing in God Almighty, believing in the day of resurrection and giving charity, doing good deeds, and avoiding evil deeds. In general, the rules in Islam cover three main things, namely aqidah, sharia, and morals. Islam positions economic activity as one of the important aspects to gain glory (falah), and therefore the economic activity needs to be guided and controlled so that it goes in tune with Islamic teachings. Economic activity can only lead to falah as long as it is carried out based on Islamic beliefs and is colored by Islamic morality.Keywords: Islam, Economic activity, Falah. AbstrakIslam merupakan wahyu yang diturunkan oleh Allah swt. kepada rasul-Nya untuk mengatur segala aspek hidup baik vertikal maupun horizontal yang berisi tuntunan kehidupan secara luas, sekaligus memberikan nilai-nilai esensial pada kehidupan tersebut. Islam juga berarti sebagai kepatuhan, ketaatan terhadap kehendak dan hukum Allah swt. dan bertaqwa kepada-Nya yang diturunkan untuk menata kehidupan manusia di dunia dan akhirat. Ajaran-ajaran Islam bersumber dari Alquran, sunnah dan ijtihad. Pokok-pokok ajaran Islam adalah beriman kepada Tuhan Yang Maha Esa, mengimani hari kebangkitan dan pembalasan amal, melakukan amal-amal kebajikan, dan menjauhi perbuatan-perbuatan yang jahat. Secara umum aturan dalam Islam meliputi tiga hal pokok, yakni aqidah, syariah, dan akhlak. Islam memosisikan kegiatan ekonomi sebagai salah satu aspek penting untuk mendapatkan kemuliaan (falah), dan karenanya kegiatan ekonomi perlu dituntun dan dikontrol agar berjalan seirama dengan ajaran Isla. Kegiatan ekonomi hanya mampu membawa kepada falah selama dilaksanakan berdasarkan akidah Islam dan diwarnai dengan moral Islam.Kata kunci: Islam, Aktifitas ekonomi, Falah.